ANALISA KINERJA LALU LINTAS RUAS JALAN SEMARANG – GROBOGAN PADA PERSIMPANGAN PASAR KARANGAWEN KABUPATEN DEMAK - Hidayat, Muhammad Mansur; Aprillianto, Hery; Rizani, Mohammad Debby; Ariawan, Donny (Universitas PGRI Semarang, 2022)
ABSTRACT. This type of research is quantitative research. The problems in this study are 1) The factors that cause traffic jams on the Semarang-Grobogan Karangawen Demak road. 2) the performance of the unsignalized intersection on the Semarang-Grobogan Karangawen Demak road. This type of research is quantitative research. Based on the analysis, the results for side resistance are 1215.2 vehicles/hour for the east direction and 1162.7 vehicles/hour for the west direction, so the side resistance class for the east and west directions is very high (VH) because the total weight is greater than 900 vehicles/hour with conditions of commercial areas and high activity on the side of the road. The level of congestion with traffic volume in the west is 3122 pcu/hour and 1686 pcu/hour in the east and a capacity of 1469.52 pcu/hour for the west and east and the degree of saturation is 0.87 for the west and 0.54 for the east direction east.Keywords: factors causing congestion, performance of unsignalized intersections.